Integrated assessment of the quality of special protective clothing for firefighters - Mynbayev M.T. Мынбаев М.Т.; Kerimkul S.E. Керімқұл С.Е.; Utesheva G.T. Утешева Г.Т. (Рroblems of engineering and professional education, 2022)
In this article, a method is proposed for a comprehensive assessment of the quality of special protective clothing for firefighters, including experimental verification of materials and theoretical studies using a mathematical model.